Medicine and death - De Caprio, Lorenzo; Di Palma, Annalisa (Medicina e Morale, 1997)
Death has had a central position in medicine in every age, but its history shows that physicians' engagement to fight for life at any cost is a peculiarity of modern scientific progress. On the other hand, in the transition of a society characterized by traditional values into a modern society, historians observe profound changes in the relationship between man and death. While culture dominated by the religious tradition accepted death as a limit of man and an integral part of the human condition, although it still protected life, the modern culture, in its anxiety to dominate the world, has removed and fights death. Therefore only interventions aimed at re-establishing human and moral values in the education of the physician can give a meaning to the practice of medicine, that fully reflects the ideology and values of a society dominated by technology and science. Technological progress has provided physicians with the means to save human lives, but without human and moral values, those very means can cause the protraction of the dying person's agony. Technological progress seems to come back against man. The bioethical debate aims to re-establish the dignity of death, but it has come to a standstill on the heart-rending problem of euthanasia. The authors believe that this situation is dangerous and in fact in this period of limited economic resources, the decisions regarding life and death are being conditioned by economic evaluations.